Association of Dry Eye Disease and Diabetic Retinopathy with Glycated Hemoglobin at a Tertiary Care Unit of Karachi Pakistan - Sultan, Sharjeel; Khanzada, Mahtab Alam; Shakeel, Ayisha; Ahmed, Nida; Fawwad, Asher; Abdul Basit (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: To investigate the association of dry eye disease and diabetic retinopathy (DR) with glycated haemoglobin at a tertiary care unit in Karachi, Pakistan. Methodology: This cross-sectional observational study was conducted at Baqai Institute of Diabetology and Endocrinology, Baqai University Karachi, Pakistan, from July to December 2020. A total of 238 subjects having type 2, type 1, and gestational diabetes mellitus participated in this study. They went through a routine ophthalmic examination, breakup tear film time (BUT) test, Schirmer I test, staining fluorescein, and fundus photography performed to diagnose the DR. Baseline detail and biochemical parameters were recorded. Data analysis was done on statistical packages for the sciences social (SPSS) 20 version. Results: A total of 72 participants had dry eye disease (DED) conforming to a total prevalence of 30.25%; 11(4.6%) had severe dry eyes, 26(10.9%) had moderate dry eyes, 35(14.7%) had mild dry eyes whereas, 166(69.7%) participants had normal eyes. There was no significant association between gender, index mass body (BMI), smoking habits, history of family diabetes, and duration of Diabetes with DED. The frequency of diabetic retinopathy (DR) was registered as 23.5%; 29(24%) males and 27(23.1%) females, respectively. Conclusion: Overall, a 30.3% frequency of dry eye in diabetic individuals was observed. It should improve by having consistent follow-ups after three to six months, providing a distinct difference in the condition compared to the non-affected individuals.